Junctional Rhythm: Cardiac Conduction Abnormalities and Clinical Implications in Nursing - Almutairi, Thallab; Baneen Ali Eassa; Samira Dhaifullah Ali Mudarba; Muneera Alhalw Alanezy; Nawal Lahiq Salman Alwadani; Mohammed Ahmed Alzahrani; Roza Saeed Alamoudi; Roaa Mahmoud Aljezani; Salwa Osamh Rashed; Norah Hussain Harthi; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Junctional rhythm is a cardiac conduction abnormality that arises when the sinoatrial (SA) node fails to function effectively, allowing the atrioventricular (AV) junction to assume pacemaker activity. Although often benign, junctional rhythms may indicate significant underlying cardiac or systemic pathology and are frequently encountered in clinical nursing practice. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This article aims to provide a comprehensive overview of junctional rhythm, focusing on its etiology, pathophysiology, clinical presentation, evaluation, management, and nursing implications. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A narrative review approach was used to synthesize current evidence regarding junctional rhythm. The article integrates anatomical, electrophysiological, clinical, and nursing perspectives, drawing from established cardiology and nursing literature to enhance clinical applicability. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Junctional rhythm occurs due to suppression or failure of SA node activity and may present at varying heart rates, including junctional bradycardia, escape rhythm, accelerated junctional rhythm, and junctional tachycardia. Clinical manifestations range from asymptomatic findings to dizziness, syncope, and hemodynamic instability, depending on heart rate and underlying cause. Electrocardiography remains the cornerstone of diagnosis, while management primarily targets correction of reversible etiologies. In severe or persistent cases, pharmacologic therapy or pacemaker implantation may be required. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Junctional rhythm represents both a protective cardiac mechanism and a potential marker of serious underlying disease. Accurate recognition and appropriate management are essential to prevent complications and optimize patient outcomes.